Strategi penanganan Non Performing Finance (NPF) pada pembiayaan murabahah di BMT - Mahmudatus Sa’diyah (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
Murabahah financing is a product with a great demand coming from the lower-middle class because the process is very simple as merely utilizes sale-and-purchase contract backed up by the collateral. The purpose of this study is to evaluate the determinant factors of Non-Performing Finance (NPF) in BMT and its management strategies. This study uses a qualitative approach. Data collection methods used in this study are interviews, observation and documentation. Data analysis techniques used are data reduction, data display, and conclusion/verification. Based on the results of the study, it can be concluded that the determinant factors of Non-Performing Finance (NPF) in BMT are mistakes done by BMT officers when performing initial analysis and survey before giving fundings led to Non Performing Finance (NPF) in BMT. The strategy undertaken by BMT in managing Non Performing Finance (NPF) is through a family-based approach, revitalization with rescheduling, management assistance, collection agents, or settlement with the collateral.